Pengembangan Media Kartu Kuartet untuk Keterampilan Menulis Kalimat Sederhana - Arfiana, Rizma; Nanang; Iqnatia; Afakh (Jurnal Riset Madrasah Ibtidaiyah, 2024)
This study aims to describe the quality of learning media produced in terms of validity and effectiveness as well as describe students' responses to quartet card learning media for simple sentence writing skills. The development of quartet card media uses the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). This research was conducted at UPT SD Negeri 23 Gresik. The subjects of this research were fourth grade students of UPT SD Negeri 23 Gresik. The techniques used for data collection are media validation and questionnaires. The data analysis techniques used were media and material expert validation analysis, student response questionnaire analysis, and media effectiveness analysis. As a result of the research, two media experts who are lecturers in the Elementary School Teacher Education study program and two material experts from classroom teachers IV UPT SD Negeri 23 Gresik declared the quartet card learning media for simple sentence writing skills to be